Line Application As A Learning Medium In Islamic Education Subjects - Rahma Diah An Nilam; Eni Fariyatul Fahyuni (UMSU, 2023)
This study aims to investigate the use of social media Line as a learning medium in Islamic Religious Education subjects. The method used in this research was classroom action research with 3 cycles. After the research, the results obtained are learning media in the form of Line applications can improve student learning outcomes with a student completion rate of 100% in cycle III. This proves that Line social media can improve student learning outcomes.